2010
DOI: 10.1007/s00586-010-1423-9
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic myelopathy due to ossification of ligamentum flavum: a retrospective analysis of predictors of surgical outcome and factors affecting preoperative neurological status

Abstract: Despite good posterior decompression of thoracic myelopathy due to ossification of ligamentum flavum (OLF), recovery varies widely from 25 to 100%. Neurological status on presentation also varies widely in different patients. We, therefore retrospectively studied relation of various clinical and magnetic resonance imaging (MRI) parameters with preoperative neurological status and postoperative recovery in 25 patients who underwent decompressive laminectomy for thoracic myelopathy due to OLF. Patients were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 29 publications
7
47
0
Order By: Relevance
“…41 A recent study evaluating the effect of intramedullary signal changes on recovery suggested that the presence or absence of signal changes did not correlate with postoperative recovery; but whenever present, intramedullary signal size (ISS) greater than 15 mm significantly compromised recovery. 39 The results of our study match with other studies 39,42 ; however, we did not evaluate the effect of ISS with recovery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…41 A recent study evaluating the effect of intramedullary signal changes on recovery suggested that the presence or absence of signal changes did not correlate with postoperative recovery; but whenever present, intramedullary signal size (ISS) greater than 15 mm significantly compromised recovery. 39 The results of our study match with other studies 39,42 ; however, we did not evaluate the effect of ISS with recovery.…”
Section: Discussionsupporting
confidence: 85%
“…Despite good posterior decompression of thoracic myelopathy due to OLF, recovery varies widely from 25 to 100%. 39 We had improvement in over 90% of our patients at their respective last follow-up.…”
Section: Discussionmentioning
confidence: 63%
“…However, outcomes after surgery may depend on the involvement of the spinal cord, irreversible changes, and duration of symptoms [29]. Sanghvi et al [31] reported that the predictors of postoperative recovery are preoperative symptom duration and intramedullary signal size. In the present study, all six patients who had undergone surgical decompression showed JOA score improvement and an average recovery rate of 58.9 %.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence the neurological recovery after decompressive surgery for cervical and thoracic myelopathy. Previous studies have suggested that the surgical outcome and prognostic factors include patient clinical characteristics (age at surgery, sex, duration of symptoms, preoperative JOA score, type of myelopathy, radiological findings, spinal cord evoked potentials type, surgical procedure, and follow-up period duration), intramedullary signal change on MRI, and outcomes of the 15-second grip-and-release test and the 10-second step test [15][16][17][18][19][20]. However, the prognostic guidelines are not clear, thus, making it difficult for the surgeon to predict neurological recovery and outcome.…”
Section: Discussionmentioning
confidence: 99%